2012
DOI: 10.1080/17470218.2011.597865
|View full text |Cite
|
Sign up to set email alerts
|

Variation in working memory capacity and cognitive control: Goal maintenance and microadjustments of control

Abstract: Variation in working memory capacity (WMC) and cognitive control was examined in four experiments. In the experiments high-and low-WMC individuals performed a choice reaction time task (Experiment 1), a version of the antisaccade task (Experiment 2), a version of the Stroop task (Experiment 3), and an arrow version of the flanker task (Experiment 4). An examination of response time distributions suggested that high-and low-WMC individuals primarily differed in the slowest responses in each experiment, consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 65 publications
(160 reference statements)
10
102
2
1
Order By: Relevance
“…Improvements in working memory functioning for persons with ADHD are particularly relevant, as they may address not only the well-documented behavioral and neural working memory impairments found in ADHD (e.g., for more detail see Fassbender et al [56], Schoechlin and Engel [57], Martinussen et al [58], Willcutt et al [59], Mills et al [60], Rapport et al [61], and Bolden et al [62]), but also some attentional control issues, as working memory capacity is, at least in part, related to degree of distractibility and cognitive control [63,64]. Thus, improvements in working memory, or conversely attentional control, may benefit the alternative, related process.…”
Section: Working Memory Trainingmentioning
confidence: 99%
“…Improvements in working memory functioning for persons with ADHD are particularly relevant, as they may address not only the well-documented behavioral and neural working memory impairments found in ADHD (e.g., for more detail see Fassbender et al [56], Schoechlin and Engel [57], Martinussen et al [58], Willcutt et al [59], Mills et al [60], Rapport et al [61], and Bolden et al [62]), but also some attentional control issues, as working memory capacity is, at least in part, related to degree of distractibility and cognitive control [63,64]. Thus, improvements in working memory, or conversely attentional control, may benefit the alternative, related process.…”
Section: Working Memory Trainingmentioning
confidence: 99%
“…There is a large and consistent body of research to indicate that individual differences in working memory capacity (WMC) refl ect basic differences in cognitive control (Engle & Kane, 2004;review in Barrett, Tugade & Engle, 2004). Nevertheless, Unsworth, Redick, Spillers and Brewer (2012) showed that variation in WMC was related to some, but not all, cognitive control operations. WMC was related to active maintenance of the goal measured by response time distributions in Stroop task and antisaccade task.…”
Section: Executive Attention and Rifmentioning
confidence: 99%
“…Derryberry & Reed, 2002) and the research on the relationship between WM and executive attention (Unsworth, Redick, Spillers & Brewer, 2012). Even if the theoretical accuracy of ACS were acceptable, the diffi cult problem of a the retrievalinduced forgetting reliability and stability of individual differences in AC has remained opened.…”
Section: Is It Correct To Use Acs For Measuring Individual Differencementioning
confidence: 99%
“…Apart from maintaining and updating goals (formulated by many authors), Cohen et al also mention conflict detection and monitoring (e.g., activating distinct responses to the same stimulus, like colored lettering in the Stroop task), as well as control micro-adjustment for repetitive task requirements (e.g., the decrease in response time in the case of incongruence between word color and meaning in the Stroop task for subsequent incongruent trials). The choice of these particular EFs was dictated by their suitability for the scope of our empirical studies considering the role of affect, as well as by the applicability of experimental results on the resource consumption associated with these EFs (Unsworth, Redick, Spillers & Brewer, 2012) to explaining the role of affective operations. These studies will be discussed later.…”
Section: Affective-cognitive Mechanisms Of Executive Functionsmentioning
confidence: 99%
“…In the meantime, I will proceed to analyze how affect participates in sequential conflict adjustment (also known as "control micro-adjustment;" Unsworth et al, 2012), which can be inferred from the Stroop task.…”
Section: The Role Of Negative Affect In Conflict-monitoring and Respomentioning
confidence: 99%